Funções executivas em crianças de 3 a 6 anos: desenvolvimento e relações com linguagem e comportamento - León, Camila Barbosa Riccardi (2015)
The assessment of cognition and behavior in early childhood education has been the subject of several studies, which suggest the importance of this school stage for children development as well as the possibility of identifying early signs predictive of future learning difficulties. Among the learning-related skills are the executive functions (EFs), which relate to behavior-oriented goals that enables people to act adaptively in the world. There is evidence that children who have better performance in EFs activities do better in school and also have better behavioral indicators. The objective of this research was to investigate the development of EFs. And their relationship with language and behavior in 3-6-year-old children. The subjects were 32 children, of both sexes, from Nursery and Levels 1 and 2, in a private school for early childhood education located in São Paulo. The instruments used to assess EFs were Trail Making Test, Computerized Stroop Test for preschoolers, Attention Test for Cancellation and EFs and Children s Regulations Inventory (IFERI). To evaluate oral language were used the Phonological Awareness Test, Peabody Picture Vocabulary Test, Words and Non-Words Repetition Test and Child Naming Test. Written language was evaluated by the recognition of letters and sounds, writing the name and reading and writing activities. Children s behavior was assessed by the Strengths and Difficulties Questionnaire (Strengths and Difficulties Questionnaire SDQ). The questionnaires were answered by children s guardians and teachers. Parametric and nonparametric analysis revealed effect of series on at least on measure of all instruments used, except IFERI-Parents, indicating that EFs tend to develop with school progression. There were several significant correlations between tests of the same skill and between different measures. In tests that assess EFS, measures that assess attention had very high and high correlations with measures of oral language and written language. This result points out that in fact EFs appear to be related to reading and writing, being important for the development of oral language and early literacy. Such relationships are considered unique, with little national and international reference about it. This result should be investigated more specifically in future research and can reveal that since very early ages, EFs are already important to the development of oral language, and vice versa, perhaps in a bilateral relationship of mutual influence. Correlation analysis between test and the answers in inventories showed few significant correlations of high magnitude, however lower scores in EFs tests tend to be more correlates to complaints in situations that assess executive functions (IFERI) and behavior (SDQ) reported by parents and in children from kindergarten, as revealed significant relationships between EFs, oral and written language and behavioral measures. Although it is no possible to derive a causal relationship, the results support the importance of identifying delays in the development of skills assessed and develop early interventions.